Retrospective evaluation of the severity of and prognosis associated with potassium abnormalities in dogs and cats presenting to an emergency room (January 2014–August 2015): 2441 cases. Issue 6 (3rd September 2019) - Hoehne, Sabrina N.; Hopper, Kate; Epstein, Steven E.
Abstract: Objective: To determine the severity, concurrent clinical signs, and disease processes associated with potassium abnormalities in dogs and cats presenting to a veterinary emergency department and associated mortality. Design: Retrospective and descriptive study over 20 months. Setting: University teaching hospital. Animals: 1916 dog and 525 cat visits. Interventions: None. Measurements and Main Results: Medical records from patients with a potassium concentration measured within 24 hours of admission were identified. Hypokalemia and hyperkalemia were defined as a potassium concentration <3.5 mmol/L [3.5 mEq/L] and >5 mmol/L [5 mEq/L], respectively. Associated disease processes and pathophysiologic risk factors for potassium abnormalities were reviewed for moderate to severe potassium abnormalities (<3 mmol/L or ≥6 mmol/L) [<3 mEq/L or ≥6 mEq/L]. Mortality associated with normokalemia, mild, and moderate to severe dyskalemia were evaluated. Overall prevalence of abnormal potassium concentration was 27% in dogs and 40% in cats. Moderate to severe hypokalemia and hyperkalemia were present in 3% of dogs and 8% of cats, and 2% of dogs and 7% of cats, respectively. Moderate to severe hypokalemia was most commonly associated with gastrointestinal disease (48% of dogs and 44% of cats) while moderate to severe hyperkalemia was most commonly associated with urinary tract disease (60% of dogs and 97% of cats). Dogs with hypokalemia and dogs and cats with hyperkalemia ( P  < 0.001) had significantly greater mortality than those with normokalemia. Dogs with mild hypokalemia and mild hyperkalemia ( P  < 0.0001) had higher mortality than dogs with normokalemia, but this was not found in cats. Conclusions: Dyskalemia was common in this population and was associated with greater mortality. Moderate to severe potassium abnormalities were uncommon in this population and occurred most frequently in animals with gastrointestinal and urinary tract disease.